Breakthroughs in Medicinal Chemistry: New Targets and Mechanisms, New Drugs, New Hopes-5 - Mangoni, Arduino A; Eynde, Jean Jacques Vanden; Jampilek, Josef; Hadjipavlou-Litina, Dimitra; Liu, Hong; Reynisson, Jóhannes; Sousa, Maria Emília; Gomes, Paula A C; Prokai-Tatrai, Katalin; Tuccinardi, Tiziano; Sabatier, Jean-Marc; Luque, F Javier; et al. (Molecules (Basel, Switzerland), 2019)
Breakthroughs in Medicinal Chemistry: New Targets and Mechanisms, New Drugs, New Hopes is a series of Editorials which is published on a biannual basis by the Editorial Board of the Medicinal Chemistry section of the journal Molecules [...].
Keywords: farmaceutická chemie; Drug Discovery; lidé; objevování léků; Humans; Chemistry, Pharmaceutical